The impacts of transcranial direct current stimulation combined with aquatic neuromuscular training on pain, function, kinesiophobia, knee instability, and quality of life in knee osteoarthritis: a double-blind randomized trial - Asma Tapeh Kaboodi; Farzaneh Gandomi; Parviz Soufivand; Shirin Assar (Journal of NeuroEngineering and Rehabilitation)
Abstract Background Knee osteoarthritis (KOA) is a significant challenge in elderly populations. Despite reporting the positive effects of transcranial direct current stimulation (tDCS) on pain reduction in patients affected by knee osteoarthritis, very few studies have investigated its efficacy in combination with aquatic neuromuscular training (ANMT). Accordingly, this study aimed to evaluate the effects of adding anodal tDCS to ANMT on pain, functional performance, kinesiophobia, joint instability, and quality of life in women with KOA. Methods This double-blind, randomized controlled trial with parallel-group and pre-test/post-test design involved 44 women diagnosed with KOA. Participants were purposively selected and randomly assigned to ANMT combined with real tDCS (r-tDCS; n = 22) or placebo (n = 22), both targeting M1. Pain was the primary outcome, assessed weekly and at the end of the six-week intervention. Secondary outcomes included functional performance, knee instability, kinesiophobia, and quality of life, measured using the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC), self-reported knee instability, the Tampa scale, and the Osteoarthritis Knee and Hip Quality of Life (OAKHQOL) questionnaire before and after the six-week interventions. The interventions consisted of 18 sessions, each lasting 20 min, followed by 60 min of ANMT. Mixed repeated measures ANOVA and one-way ANCOVA were utilized for within-group and between-group comparisons. Results A statistically significant difference in immediate effects of pain intensity between the two interventions was observed (p < 0.001, η2 p=0.35). However, no significant difference was found between groups in the short term, six weeks post-intervention (p = 0.36, η²p = 0.02). Significant differences were found between the groups in knee instability (p = 0.04, η2 p=0.10) and functional performance (p = 0.03, η2 p=0.10). However, no significant differences were observed between the groups in kinesiophobia and quality of life (p > 0.05). Conclusions Aquatic neuromuscular training combined with r-tDCS was more effective in reducing pain intensity immediately after intervention. However, no significant short-term differences were observed between the real and placebo groups. Furthermore, after six weeks, r-tDCS showed greater efficacy in improving knee instability and functional performance. Trial registration The study was prospectively registered in the Iranian Registry of Clinical Trials (IRCT20231106059975N1; Registration Date: 2024-07-08), https://irct.behdasht.gov.ir/trial/76061 .